Nutritional evaluation and flavor characteristic analysis of different parts of Clitocybe maxima - DU Jiaxin; XI Jiapei; FANG Donglu; SUN Hailan; HU Qiuhui; ZHAO Liyan (浙江大学学报. 农业与生命科学版)
Clitocybe maxima is a rare and high-temperature edible fungus with a unique flavor. In this experiment, the edible value of the pileus, stipe and mycorrhiza of the fresh C. maxima was explored and evaluated through the detections of basic nutrients and mineral contents. The taste and odor differences of different parts of C. maxima were evaluated by electronic tongue, electronic nose and gas chromatography-ion mobility spectroscopy (GC-IMS), aiming to provide a theoretical basis for flavor research of C. maxima. The results showed that the moisture, fat and protein contents were higher in the pileus and the content of total sugar in the stipe was the highest. The amino acid compositions in the pileus were in line with the Food and Agriculture Organization of the United Nations (FAO)/World Health Organization (WHO) ideal protein standard, and methionine only existed in the pileus. At the same time, the C. maxima was rich in sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), ferrum (Fe), zinc (Zn) and so on, and the element contents in different parts were different. The results of electronic tongue detection showed that the contents of bitter components in all parts of C. maxima were high. By using linear discriminant analysis (LDA) to reduce the dimensions of the electronic nose analysis results, it was found that the odor characteristics in different parts of C. maxima could be clearly distinguished. Among the 84 volatile flavor substances detected by GC-IMS, alcohols, aldehydes and ketones had significant effects on the flavor profiles of different parts of C. maxima. The contents of 1-octene-3-ol (monomer and dimer), 1,3-octadiene (dimer) and 3-methylthiopropanal (monomer and dimer) were important volatile substances that produced different flavor profiles in different parts of C. maxima, and the monomer and dimer of 3-methylthiopropanal were the characteristic flavor compounds in pileus.